USAHA KOPI BUBUK CAP KUDA TERBANG DI KELURAHAN SAWAHAN TIMUR KECAMATAN PADANG TIMUR (1984-2013) - Safitri, Yulinda - (Pendidikan Sejarah, 2014)
Home Industry of Cap Kuda Terbang coffee powder is a business run by H.Arman (Mak Datuak), which is their own business idea since 1984 to 2013, it revealed the development of coffee business in East Sawahan of East Padang District. East Sawahan was chosen as the research object because this village is a place of Cap Kuda Terbang coffee powder production in Padang. Limitation of the study was taken early in 1984 because this year was the beginning of the existence of coffee business in the East Sawahan, while the final boundary of the study in 2013 because in this year when this business can survive in the middle of the many industries that have sprung up in the coffee powder industry and demand for export from the Netherlands.This study is purposed to describe Cap Kuda Terbang coffee powder business at East Sawahan Village of East Padang District (1984-2013). This study used historical research method consists of four stages. The first stage was heuristic that is collecting the data, both primary and secondary data. The second stage was a source of criticism, it was testing and selection of the data collection. The third stage was analysis and interpretation of data that is classifying or re-interpretation of the data that have been obtained. The last was stage of historiography, it was the presentation of research results in the form of a paper or thesis. The results of this study, it can be concluded that Cap Kuda Terbang coffee powder business the East Sawahan keep growing from1984-2013 both in production, distribution and management. In the beginning phase 1984-1986, this business was viewed from production which is still using traditional equipment that produces 50 kg/week coffee powder. In distribution, the sales of this product are still distributed around Sawahan and placed in stalls of home environment. In management, it still used family labor. In the second phase in 1986-2008, it was called as period of development it can be seen from production equipment which used for processing coffee beans already used modern machine and produced 600 kg/week. Moreover, the distributions of coffee sales have reached Riau Province and Bukittinggi. In addition, the management already employs residents around East Sawahan. Last, third phase from 2008-2013 was called persist period, the production of coffee powder produced 1000 kg/week. The distribution is not only traditional in Padang markets but also available in Supermarkets and Mini market. Meanwhile, management workers are skilled people.